2014
DOI: 10.1007/s00256-014-1910-x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal origins of the long head of the biceps tendon can lead to rotator cuff pathology: a report of two cases

Abstract: Previous case reports have highlighted various anomalous origins of the long head of the biceps tendon (LHBT) that do not originate from the superior glenoid labrum or supraglenoid tubercle. Yet, these cases were all reported as incidental findings and were not thought to cause any significant shoulder pathology. We present the magnetic resonance (MR) imaging and clinical treatment of two cases where aberrant intra-articular origins of the long head of the biceps tendon from the anterior edge of the supraspina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Proposing this as one of the possible etiologies of the rotator cuff tear, they showed that when the long head of the biceps brachii was attached to the supraspinatus anterior aspect, good clinical outcome was achieved. Another study that supports the surgical treatment of variations of the long had is that of Zhang et al 8) They reported of two cases of variations of the long head that originated from the anterior aspect of the supraspinatus tendon, and suggested this as an etiological deformity that induced the tear of the supraspinatus through the input of excessive tension. In accordance to their hypothesis, tenodesis of the biceps tendon of these two patients, which reduces the excess tension on the tendons, gave good clinical outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Proposing this as one of the possible etiologies of the rotator cuff tear, they showed that when the long head of the biceps brachii was attached to the supraspinatus anterior aspect, good clinical outcome was achieved. Another study that supports the surgical treatment of variations of the long had is that of Zhang et al 8) They reported of two cases of variations of the long head that originated from the anterior aspect of the supraspinatus tendon, and suggested this as an etiological deformity that induced the tear of the supraspinatus through the input of excessive tension. In accordance to their hypothesis, tenodesis of the biceps tendon of these two patients, which reduces the excess tension on the tendons, gave good clinical outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, these studies give a mixed message for the treatment of anatomic variations of the biceps brachii long head. However, when we consider that the rotator cuff tears of the cases described by Ogawa and Naniwa 7) and Zhang et al 8) cannot solely be explained by anatomic variations of the long head, it is difficult to implicate anatomic variations as being the direct causative factor and erroneously conclude a benefit of surgical interventions. This is because Ogawa and Naniwa 7) sought to prove a clinical significance of disconnecting a long head using an already disconnected one, and Zhang et al 8) studied subjects, currently active young volleyball and baseball athletes, wherein it is difficult to preclude sports-related injuries as etiology for the rotator cuff tear.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation